2016
DOI: 10.14740/wjnu237w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Post-Ureteric Reimplantation Urinary Tract Infection in Primary Vesicoureteral Reflux

Abstract: Background: The goal of treatment in vesicoureteral reflux (VUR) is to reduce the risk of reflux-associated pyelonephritis. Medical versus surgical treatment for VUR is still controversial, with surgery successful in majority of cases. There are not enough data available in literature on long-term incidence of urinary tract infection (UTI) after reimplantation. The aim of the study was to determine the long-term outcome after reimplantation with respect to UTI, renal scarring and potential risk factors for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Mariyappa et al [19] reported an fUTI rate of 4.9% after a mean follow-up period of 42 months. In addition, the risk of post-reimplant UTI continued into adult life.…”
Section: Discussionmentioning
confidence: 99%
“…Mariyappa et al [19] reported an fUTI rate of 4.9% after a mean follow-up period of 42 months. In addition, the risk of post-reimplant UTI continued into adult life.…”
Section: Discussionmentioning
confidence: 99%